Pengembangan Prototipe Aplikasi Peminjaman dan Pengembalian Barang Menggunakan Model SDLC - Gimnastiar, Alfin; Gading, Rafli Arya (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2026)
The management of borrowing and returning goods in government institutions is still largely carried out manually, which often gives rise to various problems, such as difficulties in tracking borrowing histories, the high risk of recording errors, and the lack of transparency regarding the availability of goods. This condition indicates the need for support from an information system that is capable of assisting the recording process and inventory management in a more structured, systematic, and easily monitored manner. This research aims to design a prototype of a goods borrowing and returning application as an initial solution to these problems as well as a preliminary representation of a system that can be further developed by the institution. The research method used is a Research and Development (R&D) approach with a prototype Software Development Life Cycle (SDLC) model, which allows system development to be carried out gradually and flexibly in accordance with user needs. Data collection was conducted through observation and interviews to obtain an overview of the ongoing work processes and to identify the required system needs. The collected data were then analyzed as the basis for designing the system workflow, data structure, and user interface design. The results of this research are in the form of an application prototype that represents the main system features, including goods borrowing, goods returning, availability checking, goods data management, and report generation.